Prosperity and Stagnation in Capitalist Economies - Toichiro Asada; Peter Flaschel; Peter Skott (University of Massachusetts, Department of Economics, 2005)
The KMG growth dynamics in Chiarella and Flaschel (2000) assume that wages, prices and quantities adjust sluggishly to disequilibria in labor and goods markets. This paper modifies the KMG model by introducing Steindlian features of capital accumulation and income distribution. The resulting KMGS(teindl) model replaces the neoclassical medium- and long-run features of the originalKMG model by a Steindlian approach to capital accumulation, as developed in a paper by Flaschel and Skott (2005). The model is of dimension 4 or 5, depending on the specification of the labor supply. We prove stability assertions and show that loss of stability always occurs by way of Hopf-bifurcations. When global stability gets lost, a nonlinear form of the Steindlian reserve army mechanism can ensure bounded dynamics. These dynamics are studied numerically and shown to exhibit long phases of prosperity, but also long phases of stagnant growth. JEL Categories: E24, E31, E32.
Keywords: 330; KMGS dynamics; accelerating growth; stagnant growth; normal / adverse income shares adjustment; reserve army mechanisms